A Study on the Transferable Skills of the Engineering Students at Universiti Tun Hussein Onn Malaysia - Jamil Abd Baser; Azman Hasan; Aifaa Husna Asha’ri; Moh. Khairudin (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The purpose of this study was to identify the students' levels of awareness of the importance of transferable skills and the mastery of the aspects of adaptive, critical thinking, and problem-solving. In addition, this study also aimed to identify differences in students' levels of awareness of the importance of transferable skills and the difference levels of awareness between male and female students. Research method used in this study was quantitative survey by using questionnaire. Data were analysed by finding the mean and an independent t-test. The results showed that  students' levels of awareness of the importance of transferable skills and the mastery levels of these skills were at a high and there were significant differences between female and male students' levels of awareness of the importance of transferable skills. However, the analysis showed no difference in the levels of dominance. Overall, greater awareness will help students to master the skills perfectly. It can also be used as a guide for students to identify elements and features that are required by employers nowadays.